RADIOACTIVITY OF GRANITIC ROCKS FROM NORTHERN GREECE - Papadopoulos, A.; Christofides, G.; Papastefanou, C.; Koroneos, A.; Stoulos, S. (Bulletin of the Geological Society of Greece, 2010)
Forty-nine samples from several plutons in northern Greece have been studied for their activity concentrations of 40K, 226Ra and 232Th by using gamma-ray spectroscopy. The activities of 40K, 226Ra and 232Th of the majority of the samples exceed the average level of these radionuclides in soil and building materials. Samples of basic composition have very low concentrations of radionuclides while intermediate and acid rocks are more enriched in 40K, 226Ra and 232Th and their decay products. In order to assess the radiological impact from the investigated rocks, absorbed gamma dose rate (Da), annual effective dose (HE), activity index (AI) and gamma-ray index (Iγ) were estimated. The activity concentrations and hazard indices were compared to those of plutonic rock samples from all over the world, as well as other building materials. The average of hazard indices of Greek granites is below ‘world’ average in all cases. Moreover, it is still bellow the criteria of UNSCEAR (2000). Therefore, at least from radiological point of view and for the investigated rocks, the use of granites from northern Greece as building materials is recommended.